Estabilidade no desempenho de três diferentes técnicas de salto vertical - Ramon Franco Carvalho; Ercole da Cruz Rubini; Leonardo Ferreira Cabral (Universidade Estadual do Oeste do Paraná, 2014)
To study reliability of vertical jump (VJ) is to test the consistency of this measure to certify the quality of the data. The aim of this study was verify the stability of three different techniques of VJ. Twenty two men (22,5 ± 2,7 years; 174,3 ± 7,0 cm; 71,3 ± 8,2 kg) was tested in four occasions. The VJ carried through in the present study was squat jump (SJ), drop jump (DJ) and countermovement jump (CMJ). The first visit was used for familiarization. The subsequent visits served to collect the data of VJ in a jump platform. Four maximum jumps of each model of VJ was executed in all the visits of random form, with worst jump had been discarded of each different techniques of SV. The intervals between jumps was 45 s and between the different techniques VJ was 5 min. The variable measured were height of the jump, peak power absolute and relative to body mass. For the DJ, beyond the variable already cited, were collected the contact time, flight time and reactive strength index. To test the reliability the CCI were used. LA95% proposed by Bland-Altman was used to identify random error and a ANOVA with repeated measures followed by Bonferroni post hoc test was used to observe the systematic bias. The results had demonstrated high reliability and lower random error and systematic bias for all variables tested. The VJ are reliability measurement tools to evaluate the height of the jump, the muscular power and the reactive strength of the inferior members.